Apology and Restitution: The Psychophysiology of Forgiveness After Accountable Relational Repair Responses - Witvliet, Charlotte V. O.; Root Luna, Lindsey; Worthington, Everett L.; Tsang, Jo-Ann (Frontiers in Psychology, 2020)
Apology and restitution each represent wrongdoers’ accountable repair responses that have promoted victims’ self-reported empathy and forgiveness in crime scenario research. The current study measured emotional and stress-related dependent variables including physiological measures, to illuminate the links between predictors of forgiveness and health-relevant side effects. Specifically, we tested the independent and interactive effects of apology and restitution on forgiveness, emotion self-reports, and facial responses, as well as cardiac measures associated with stress in 32 males and 29 females. Apology and restitution each independently increased empathy, forgiveness, gratitude, and positive emotions, while reducing unforgiveness, negative emotion, and muscle activity above the brow (corrugator supercilii, CS). The presence of a thorough apology—regardless of whether restitution was present—also calmed heart rate, reduced rate pressure products indicative of cardiac stress, and decreased muscle activity under the eye (orbicularis oculi, OO). Interactions pointed to the more potent effects of restitution compared to apology for reducing unforgiveness and anger, while elevating positivity and gratitude. The findings point to distinctive impacts of apology and restitution as factors that foster forgiveness, along with emotional and embodied changes relevant to health.